Translation in the European Parliament: The Study of the Ideational Function in Technical Texts (EN/FR/ES) - Veroz, María (Meta, 2017)
In this paper we tackle the study of European Parliament technical texts in three languages, namely English-Spanish-French, focusing on their discursive features and, more concretely, on the way in which the ideational function is expressed in them. To achieve this end, we have followed the frame of the Systemic Functional Grammar compiling a trilingual parallel corpus composed of technical texts downloaded from the European Parliament (EP) Website.In accordance with the analysis proposed it is proved that these texts are characterized by a predominance of material processes, in particular, actions linked to the legal, administrative and economic world like adopt, approve, modify, create, transmit, publish, establish and sign, with their respective equivalents in Spanish and French. Although there are certain processes – mental (cognition) and verbal ones – that could have a mixed nature, as we have observed that equivalents are exchanged with each other in the different linguistic versions studied.Regarding the participants (agent, affected, recipient, beneficiary and sayer), most of them are institutions and acts/documents, when these participants in these processes are usually humans. We conclude that knowledge of these features could be useful for EU translators and should be used in the training of future translators as a guide in the translation process.